Introduction to the Special Research Forum on the Management of Organizations in the Natural Environment: A Field Emerging From Multiple Paths, With Many Challenges Ahead - Starik, Mark; Marcus, Alfred A. (Academy of Management Journal, 2000)
An increasing amount of high-quality research has been conducted in the past decade on the topic of managing organizations in the natural environment. The authors trace this evolution using path an...